Ten practical guidelines concerning the treatment of lymphoedema of the lower extremities - Spannbauer, Anna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2007)
In this paper, basic principles of complex physiotherapy in the treatment of lymphatic oedemas, particularly lymphatic drainage and general guidelines on how to prevent the progress of this disease, are presented. It is stressed that therapy is long lasting and results are not always satisfactory. In order to achieve positive results it is necessary to have a team consisting of the doctor, physiotherapists, nurses and psychologists.